PROMOTING SUSTAINABLE SOLID WASTE MANAGEMENT: A CRITICAL ANALYSIS OF DEVELOPMENT SUPPORT COMMUNICATION INITIATIVES FROM DIVERSE REGIONS - Syeda Afsheen; Professor. Dr. Fouzia Naz (International Journal of Contemporary Issues in Social Sciences, 2024)
This research paper provides a critical overview and analysis of development support communication initiatives implemented across various countries worldwide. The DSC project focused on inducing behavioral change to lead towards sustainable solid waste management practices are the main area of concern for this research paper. The study scrutinizes a total of 10 Development Communication Support (DCS) projects executed in diverse regions over the past decade (2013-2023). Five categories and coding framework is developed to analyze the contents of the selected DSC projects for this research study. The main categories include goals, communication strategies, stakeholders involved, behavioral change initiates and impact indicators. The analysis of the selected projects revealed that in many countries of the world, authorities are making use of advanced communication tools to bring sustainability in the solid waste management system. The analysis also helped in identifying that there is considerable shift in the communication approach of DSC projects concerning solid waste management as the behavioral change of citizens has become a main area of concern for the policy makers and authorities. The research paper concludes the DSC projects are significantly working on fostering behavioral change among the masses all over the world because the global community has realized that without active participation and attitude change of citizens, it is not possible to anticipate sustainability within the solid waste management systems. However, there is still need of giving more attention towards behavioral change among citizens and promoting waste sorting at user end to support recycling sector and organic compost practices.